Complex Cases in Total Knee Arthroplasty A Compendium of Current Techniques (Springer International Publishing, 2018)
Covering both primary and revision total knee arthroplasty (TKA), each technique-oriented chapter in this book opens with a clinical case and an overview of the challenges and multiple options for management, and each section within the chapter will describe the physical exam, surgical approach, clinical outcome and recent supporting literature. Chapters will utilize bullet points for quick reference and plentiful intra-operative photos to illustrate the various techniques described. Part one covers primary TKA, with cases demonstrating management strategies for the varus and valgus knee, flexion contracture, patellofemoral arthritis, and extra-articular deformity, among others, while part two covers revision TKA, with cases demonstrating acute infection, flexion and global instability, severe tibial and femoral bone loss, and periprosthetic fracture, among others. Written and edited by experts in the field, Complex Cases In Total Knee Arthroplasty: A Collection of Current Techniques will be a useful reference for orthopedic surgeons, residents and fellows as well as sports medicine specialists and anyone involved in surgical care of the knee.